USC-Basic Education Department’s Collaborative SHS Program (A Hybrid Grades 11 and 12 Model) - Javines, Felino B (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2015)
When President Benigno Aquino III signed into law Republic Act 10533 or the Enhanced Basic Education Act of 2013, this signals an insistent educational reform that will make academic stakeholders conscious of the quality of graduates they produce. This goes to show that the government is assertive in improving the quality of our educational system to be at par with international standards. Thus, Education was significantly prioritized and given importance. One of the most challenging features of K to 12 is the establishment of the Senior High School program. It is then the purpose of this paper is to present the Grade 11 and 12 model of the University of San Carlos Basic Education Department under the Technical Vocational (Tech-Voc) Track. The project is collaboration between two institutions with distinct orientation. Tech-Voc Track is one of the four identified tracks of the K to 12 Program under Senior High School with Academic Track, Sports Track and Arts and Design completing the list. This collaborative technical vocational track is also rooted in the country’s education strategy which is anchored on the National Education for All (EFA) 2015 Plan and attainment of the Millennium Development Goals (MDG’s) which aim to provide an overarching policy framework for basic education with a vision that all Filipinos will acquire basic competencies. Significantly it is also pegged in the objectives of the K to 12 Program specifically the items that state – “ be adequately prepared for the world of work or entrepreneurship or higher education and “be legally employable with potential for better learnings.